A Rare Unilateral Variation in the Course of External and Internal Carotid Arteries. - Satheesha BN; Srinivasa RS; Swamy RS; Deepthinath R; Sudarshan S; Naveen K (Department of Surgery, UKM Medical Centre, 2014)
Vascular variations in the neck region are not uncommon. Knowledge of incidence of morphological variations in the course and branching of the carotid arteries is important for radiological interpretation and surgical correction when they are symptomatic. Internal carotid artery (ICA) is known to show elongation in its extra cranial course. Previous studies have demonstrated the incidence and clinical symptoms of this morphological entity. However, the occurrence of elongation and looping of the external carotid artery (ECA) is seldom reported in the literature. During regular dissections, we came across a rare case of unilateral morphological variation of both ECA and ICA, in a male cadaver aged about 55 years. ICA presented a curved course with convexity directed posteriorly, at the level of the C2-C3 vertebrae. ECA presented a pronounced kinking or coiling, one inch below the level of the angle of the mandible. In addition, a linguo-facial trunk arising from the ECA also presented a pronounced kinking throughout its entire length.